TETRAHEDRAL AND OCTAHEDRAL COMPLEXES OF MN2+ IN THE AQUEOUS SOLUTIONS OF MNCL2.4H2O - Petkova, Petya; Nedkov, Vesselin; Tacheva, Jordanka; Vasilev, Petko; Hristov, Dian; Nedelcheva, Genoveva; Dimitrov, Ivaylo; Ivanov, Atanas; Ahmed, Ibrahim (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this work, the absorption spectra of the aqueous solutions of MnCl2.4H2O are investigated. The concentration of these solutions is in the interval 30-38 %. The experiment is conducted at the room temperature in the spectral region 350 – 650 nm. The asymmetric vibration values and the strength of the oscillator are calculated for all investigated aqueous solutions.